General Information About Means of Monitoring Student Progress - Gulbahor Makhdievna Mansurova (Miasto Przyszłości, 2024)
In education, knowledge control is one of the main elements of assessing the quality of work of both the teacher and the student. Teachers daily monitor the educational activities of their students, using various forms and methods of control. The article discusses general information about means of monitoring student progress.